6.Validity of MRI Measurements in Lumbar Spinal Canal Stenosis (Iraqi Journal of Medical Sciences, 2019)
Background:Lumbar spinal canal stenosis results from compression of spinal cord and/or nerves at any level of lumbar vertebra. The relationship between clinical features of the patients and the degree of stenosis is not clear and there is no accepted “gold standard” for the diagnosis of lumbar stenosis.Objective:To evaluate the relationship between the degree of radiologically confirmed stenosis and the severity of Oswestry disability Index and to assess the most valid parameter for the diagnosis of the lumbar stenosis.Methods;A cross-sectional study conducted on randomly selected patients with lumbar stenosis at Magnetic Resonance Image Unit of Al-Imamein Al-Kadhimein Medical City in Baghdad from May to September 2018. All patients filled Oswestry disability Index questionnaire and underwent examination using 1.5 Tesla magnetic resonance unit (Avanto, SIEMENS).Results:A total of 41 patients were included (51.46±12.62) years of age. The measurements of spinal canal including the cross-sectional area of dural sac at intervertebral levels, stenosis ratio, and depth of lateral recesses are found to be correlated significantly with the level of disability assessed by Oswestry disability Index. At all levels, neither the cross-sectional area of the lateral recesses nor Ligamentous interfacet distance correlated significantly to the level of disability.Conclusion:Magnetic resonance image measurements of spinal canal correlated to the level of disability. Stenosis ratio and cross-sectional area of dural sac at intervertebral disc were more sensitive measurements for lumbar stenosis than other parameters.Keywords: Oswestry disability Index, Spinal stenosis, magnetic resonance imageCitation: Al-Jaberi HKH, Shakir BK, Hjazeen AA. Validity of MRI measurements in lumbar spinal canal stenosis. Iraqi JMS. 2019; 17(2): 126-134. doi: 10.22578/IJMS.17.2.6
Keywords: Oswestry disability Index; Spinal stenosis; magnetic resonance image